2020
DOI: 10.1111/jocd.13349
|View full text |Cite
|
Sign up to set email alerts
|

Two multinational, observational surveys investigating perceptions of beauty and attitudes and experiences relating to aesthetic medical procedures

Abstract: Background Data on opinions and experiences of aesthetic medical procedures outside the United States and Western Europe are scarce. Aims This study aimed to survey users and non‐users of aesthetic procedures in countries where this information is less readily available, to understand attitudes and perceptions relating to beauty. Patients/Methods Two independent internet‐based observational surveys were conducted. Survey 1: individuals from Colombia, Lebanon, Malaysia, Russia and Turkey who were ‘users’ or ‘no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…Previous studies have observed that facial appearance appears critical to physical attractiveness (Shridharani, 2019), with the face reported as the most important feature for overall appearance (Mares et al, 2010). Our observations were contrary to the reports of the eyes as the most attractive part of the body by Lerner et al (1976) and the findings of two multinational observational surveys that investigated perceptions of beauty, where respondents rated the eyes and smile as the most pleasing facial feature (Redaelli et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have observed that facial appearance appears critical to physical attractiveness (Shridharani, 2019), with the face reported as the most important feature for overall appearance (Mares et al, 2010). Our observations were contrary to the reports of the eyes as the most attractive part of the body by Lerner et al (1976) and the findings of two multinational observational surveys that investigated perceptions of beauty, where respondents rated the eyes and smile as the most pleasing facial feature (Redaelli et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…The quality and quantity of information, as well as communication with a medical professional, influence the perception of medical treatment, and the community and family play an important role in decision-making. [ 22 , 23 ] Losing patient confidence is a potential risk in the field of cosmetic surgery. [ 24 ] While people may seek to identify who can be trusted for such surgery, they may be confused due to the extensive marketing used.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Providing sufficient information to patients is also a major determinant of treatment satisfaction. [ 23 ] In this study, participants also recommended careful decision-making for cosmetic surgery, after a sufficient consideration period and adequate consultation with a medical institution. Provision of sufficient education before selective cosmetic surgery contributes to minimizing patient complaints.…”
Section: Discussionmentioning
confidence: 99%
“…3 Motivation for aesthetic procedures is influenced by physical, psychosocial, psychological, and emotional factors as well as age. 4 A study of women's selfreported motivations for cosmetic procedures revealed that "look younger or fresher," "look better, prettier or more attractive to one's self," and "maintain current appearance longer" were consistently cited as key reasons. 5 While the perceived beauty of these study subjects is unknown, our personal observations suggest that beautiful women and men struggle more with the aging process than their less attractive counterparts and, in extreme cases, obsess over maintaining their physical appearance.…”
mentioning
confidence: 99%
“…3 Motivation for aesthetic procedures is influenced by physical, psychosocial, psychological, and emotional factors as well as age. 4 A study of women's self-reported motivations for cosmetic procedures revealed that “look younger or fresher,” “look better, prettier or more attractive to one's self,” and “maintain current appearance longer” were consistently cited as key reasons. 5…”
mentioning
confidence: 99%